(3PNQ GdeYGO aj eYGQVI HGfJ SYGOs - (3GdUfgGLj GdHhUjQj GdeUQj, CHh YHO Gddg, TQa GdOjf , eMeO Hf SYjO Hf MeGO Hf YHO Gddg, (B696 (3g`s ((3ehQhj MGaX eMeO UGOb Yhfjs)
(3ChdgG (B:s
(3PNQ GdeYGO aj bQQ HGfJ SYGO dCHj YHO Gddg eMeO GdHhUjQj Edi eJi CfJ HGddPGJ eTZhd hCfJ Yf cd eG bOeJ eSFhds
(3BNQgG (B:s
(3eG dG VhA UHGM hGfJTQf Hg ef GdchGcH bfOjd abfOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 139s
(3eYLe GdeDdajf(B: 3 / 317s
(3cTa GdXfhf(B: 1 / 823s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs